59.2k views
0 votes
Use the definition of the Laplace transform for cos(2t) =>
\int\limits^a_b { e^(-st)cos(2t) } \, dx where a is ∞ and b is 0

User LoLance
by
6.7k points

1 Answer

2 votes
This is really just an exercise in integrating by parts. If


\mathcal I=\displaystyle\int_0^\infty e^(-st)\cos2t\,\mathrm dt

and setting
u=e^(-st) and
\mathrm dv=\cos2t\,\mathrm dt, it follows that


\mathcal I=\displaystyle\left(\frac12e^(-st)\sin2t\right)\bigg|_(t=0)^(t\to\infty)-\frac1{4s}\left(e^(-st)\cos2t\right)\bigg|_(t=0)^(t\to\infty)-\frac1{4s^2}\mathcal I

\mathcal I=\frac1{4s}-\frac1{4s^2}\mathcal I

(4s^2+1)/(4s^2)\mathcal I=\frac1{4s}

\mathcal I=\frac s{s^2+4}
User Dan Beam
by
7.1k points